Managerial Support, IT Infrastructure, and Human Resource Competency in Information Technology Policy Implementation - Suwalas Daya Guna; Ida Bagus Made Agung Dwijatenaya; Musmuliadi Musmuliadi (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2026)
This study examines the effects of managerial support, information technology infrastructure, and human resource competency on the implementation of information technology use policy in the public sector. A quantitative research design was employed using a multiple regression approach to assess both partial and simultaneous effects among the variables. The study involved 60 respondents from a government communication and informatics institution. The findings indicate that managerial support, the availability of information technology infrastructure, and human resource competency each show positive but statistically insignificant partial effects on policy implementation. However, when examined simultaneously, the three variables demonstrate a positive and significant effect on the implementation of information technology use policy. These results suggest that policy implementation in digital government settings is not determined by a single organizational factor, but rather by the collective contribution of institutional support, technological readiness, and workforce capability. The study highlights the importance of strengthening digital leadership, improving internal coordination, ensuring infrastructure adequacy, and enhancing staff competency to support more effective policy implementation. The findings also imply that future research may benefit from incorporating mediating or moderating variables and applying qualitative or mixed-method approaches to obtain a more comprehensive understanding of policy implementation in public organizations.